Journalist-Victim Relationship: Analysis of Cyber Media Reporting on the Land Conflict of the Sunda Wiwitan Indigenous Community - Ahmad Junaidi; Sarwititi Sarwoprasodjo; Didik Suharjito; Ika Yuliasari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The relationship between journalists and sources influences reporting on conflicts in media. The news media's portrayal of conflicts can shape public opinion, which in turn can influence policy decisions. Governments and other stakeholders often pay close attention to media coverage and public reaction when making decisions related to conflicts. This study analyzes how the relationship between journalists and sources, in this case the victims from the Sunda Wiwitan indigenous community in Cigugur, West Java, in online media, relates to the land conflict and how it influences the resolution of the case. The researcher chose the theme of Sunda Wiwitan in relation to online media and conflict because the land conflict involving the Sunda Wiwitan indigenous community in Cigugur, West Java, is an issue that has received widespread media attention. Online media, with its fast and broad reach, often covers this conflict, although frequently in the form of short news pieces (hard news). This study uses a qualitative approach, employing a mixed method of content analysis, in-depth interviews which involving journalists and members of Sunda Wiwitan Community. The researchers analyze 113 news articles from national and local online media about the Sunda Wiwitan land conflict from 2020-2022. This study aims to examine how the relationship between victims in land conflicts and influential journalists affects media framing and agenda-setting.The research shows cyber media are interested to cover the issue as it carries news value of conflict and produce more news in form of hard news that features. The communication established between journalists or the media and victims or sources from the Sunda Wiwitan indigenous community influences the formation of media agendas and framing.The significant attention from online media and diverse sources influenced policy decisions regarding the Sunda Wiwitan land conflict.